Britain and The Rwandan Genocide of 1994 in A Critical Analysis: The Major Arguments of Hazel Cameron’s Book - Tarrósy, István (Afrika Tanulmányok / Hungarian Journal of African Studies, 2017)
Tarrósy István a következő művet mutatta be: Hazel Cameron: Britain’s Hidden Role in the Rwandan Genocide. The Cat’s Paw. Abingdon: Routledge, GlassHouse, 2013